2016
DOI: 10.1140/epja/i2016-16357-9
|View full text |Cite
|
Sign up to set email alerts
|

Heavy quark potential and jet quenching parameter in a D-instanton background

Abstract: Using the AdS/CFT correspondence, we study the heavy quark potential and the jet quenching parameter in the near horizon limit of D3-D(-1) background. The results are compared with those of conformal cases. It is shown that the presence of instantons tends to suppress the heavy quark potential and enhance the jet quenching parameter.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
(55 reference statements)
1
9
0
Order By: Relevance
“…In other words, the inclusion of the gluon condensation enhances the jet quenching parameter. Interestingly, it was argued [29] that the D-instanton density (closely related to the chiral condensation and the gluon condensation) also enhances the jet quenching parameter.…”
Section: Jet Quenching Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the inclusion of the gluon condensation enhances the jet quenching parameter. Interestingly, it was argued [29] that the D-instanton density (closely related to the chiral condensation and the gluon condensation) also enhances the jet quenching parameter.…”
Section: Jet Quenching Parametermentioning
confidence: 99%
“…Also, this parameter has been addressed in some AdS/QCD models [20,21]. For related results, see [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one expects that the results obtained from this theory should shed qualitative insights into analogous questions in QCD. Due to this characteristic, many quantities have been studied in the D-instanton background, such as phase transitions [32], flavor quark [33], heavy quark potential and jet quenching parameter [34].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the presence of the D-instanton density tends to increase the drag force and decrease the diffusion coefficient, reverse to the effects of the velocity and the temperature. Interestingly, it was argued that [29] the D-instanton density enhances the jet quenching parameter. Thus, one concludes that the effects of D-instanton density on the drag force and the jet quenching parameter are consistent.…”
Section: Discussionmentioning
confidence: 99%